MEKANISME KLORINASI EUGENOL MENGGUNAKAN KLORIN (CL2) DENGAN KATALIS FECL3 DALAM PELARUT DIKLOROMETANA - Sayekti, Endah; Silalahi, Imelda H; Awalliah, Emy (Program Studi Kimia Jurusan Pendidikan Kimia FPMIPA UPI, 2013)
Chlorination of eugenol by chlorine with catalyst of FeCl3 in dichloromethane solvent had been performed. Chlorination was carried out at 2oC for 5 hours. The reaction produced dark brown clot which was soluble in methanol, acetone, ethyl acetate, dichloromethane and chloroform but insoluble in aquadest. An infrared analysis gave the chlorobenzene groups at 1095.57-1072.42 cm-1. The NMR1H showed the CHCl and CH2Cl groups at 3.2884-3.0185 ppm and NMR13C showed carbon as C-Cl at 100-20 ppm. GC-MS spectrum analysis showed there are four dominant products with the time retention at 28.650; 29.300; 32.383 and 37.242. Result of the spectroscopy analysis showed that the main coumpound of eugenol chlorination were 4-(2,3-dichloroprophyl)-2-methoxyphenol (24,67%); 4-(2-chloroprophyl)-6-chloro-2-methoxyphenol(20,57%); 4-(2,3-dichloroprophyl)-6-chloro-2-methoxyphenol (13,65%) and 3,6-dichloro-4-(2,3-dichloropropyl)-2-methoxyphenol or 5,6-dichloro-4-(2,3-dichloropropyl)-2-methoxyphenol (9,92 %). Therefore, based on all analysis which were done, it can conclude that chlorination of eugenol using chlorine catalyzed by FeCl3 in dichloromethane cause addition and aromatic electrofilic substitution. Key Word: Eugenol, Chlorination, FeCl3, Dichloromethane